Modelo de doença de parkinson em camundongos baseado na injeção unilateral 6-hidroxidopamina no estriado: caracterização do curso temporal das alterações comportamentais e da degeneração nigroestriatal - CARDOSO, Váldina Solimar Lopes (Universidade Federal do Pará, 2017)
Parkinson‘s disease (PD) is a common neurodegenerative disease that affects mainly elderly people. It is characterized by the progressive cell death of dopaminergic neurons in the nigrostriatal system, which causes the development of the classic tetrad of symptoms: resting tremor, muscular rigidity, bradikynesia and postural instability. There is evidence that both genetic and environmental factors play a role in the development of the disease. In order to better understand the mechanisms undelying this disease, several animal models have been used to mimic some aspect of the dopaminergic degeneration. The intracerebral injection of 6-OHDA has been one of the most used PD model. This toxin is preferentially injected into the striatum or in the substantia nigra to provoke a selective degeneration of dopaminergic neurons from the nigrostriatal pathway. When a unilateral injection is used, the animals display a stereotypical rotational behavior after pharmacological induction, and such behavior has been largely used as a measure of the degree of nigroestriatal degeneration. This model is well characterized in rats and has been an useful tool to test neuroprotective therapies. Mice, as much as rats, are also largely used in studies of DP, but the 6-OHDA model has not been well described. The objective of the present work was to improve the characterization of the hemiparkinsonism model based on a single unilateral intraestriatal injection of 6-OHDA in C57BL6 mice, to provide a more detailed evaluation of the temporal course of the neuronal dopaminergic degeneration in the substantia nigra and to establish the degree of correlation between the degeneration and behavioral changes. Our results showed that a single injection of 10 μg of 6-OHDA into the striatum causes progressive degeneration of nigral dopaminergic neurons dependent of survival time, and that there is a high correlation between the rate of degeneration and the rotational behavior induced by apomorphine. Spontaneous motor behaviors such as ambulation and rearing had a lower correlation with the degeneration. Therefore, we suggest that the rotational behavior induced by apomorphine provides a good measure of the degree of asymmetry in the nigrostriatal pathway of mice with 6- OHDA-induced hemiparkinsonism and that it can indeed be an useful tool in experiments to test therapies with neuroprotective potential for Parkinson’s disease.